2022
DOI: 10.3390/cells11203250
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Indole-3-Acetic Acid Synergistically Regulate Plant Growth and Stress Resistance

Abstract: Plant growth and development exhibit plasticity, and plants can adapt to environmental changes and stress. Various phytohormones interact synergistically or antagonistically to regulate these responses. Melatonin and indole-3-acetic acid (IAA) are widespread across plant kingdom. Melatonin, an important member of the neuroendocrine immune regulatory network, can confer autoimmunity and protect against viral invasion. Melatonin functions as a plant growth regulator and biostimulant, with an important role in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…IAA acts as a signal between rhizobium and plants. Experimental studies have demonstrated the application of Stenotrophomonas maltophilia Sg3, Proteus mirabilis BjB17, Providencia rettgeri AlDp5, Bacillus thuringiensis TNJbx.3.3 and Bacillus cereus GR12 , which are capable of synthesizing IAA, increased the number of pods of edamame beans ( Zhang et al., 2022 ). The secretion of root in Arabidopsis can trigger Falciphora oryza to produce IAA, thus promoting the development of the lateral root of Arabidopsis ( Sun et al., 2020 ).…”
Section: Plant Growth Promotersmentioning
confidence: 99%
See 3 more Smart Citations
“…IAA acts as a signal between rhizobium and plants. Experimental studies have demonstrated the application of Stenotrophomonas maltophilia Sg3, Proteus mirabilis BjB17, Providencia rettgeri AlDp5, Bacillus thuringiensis TNJbx.3.3 and Bacillus cereus GR12 , which are capable of synthesizing IAA, increased the number of pods of edamame beans ( Zhang et al., 2022 ). The secretion of root in Arabidopsis can trigger Falciphora oryza to produce IAA, thus promoting the development of the lateral root of Arabidopsis ( Sun et al., 2020 ).…”
Section: Plant Growth Promotersmentioning
confidence: 99%
“…However, endogenous JA-Trp plays a minor role in the regulation of plant growth ( Staswick et al., 2017 ). Additionally, Trp can be converted to melatonin by L-Trp decarboxylase (PSID) and tryptophan-5-hydroxylase (CYP71P1) ( Zhang et al., 2022 ). This conversion has been found to have an effect on plant growth, such as promoting root growth after germination ( Park and Back, 2012 ), influencing flowering time and regulating plant sugar metabolism ( Zhao et al., 2015 ; Lee et al., 2019 ).…”
Section: Plant Growth Promotersmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant growth, development and differentiation are regulated by growth hormones either by inhibition or improvement in a variety of metabolic processes (Naeem et al, 2004). Of different plant hormones reported in the literature, indole acetic acid plays a critical role in cell division and elongation, as well as in several other physiological functions involved in plant growth and development (Aloni et al, 2006;Tian et al, 2014;Zhang et al, 2022). It is believed that it plays a significant role in the regulation of stress tolerance in plants subjected to various stressful cues.…”
Section: Introductionmentioning
confidence: 99%